Influence of Stress on Soil-water Characteristic Curve of Intact Loess. Issue 3 (December 2018) - Zhong, Xiumei; Wang, Qian; Liu, Zhaozhao
Abstract: The soil-water characteristic curve plays a significant role in describing the unsaturated soil characteristics, and is greatly affected by stress state, wetting and drying cycles and other factors. Accurate measurement of soil-water characteristic curve is the key to the unsaturated soil mechanics studies. In this paper, based on the GCTS soil-water characteristic curve (SWCC) instrument, the undisturbed loess was tested to study the effects of one-dimensional consolidation stress, stress history and wetting and drying cycles on the soil-water characteristic curve of undisturbed loess. The experimental results show that: (1) As the one-dimensional axial stress increases, the air intake of the soil sample gradually increases, and the decrease of the water content slows down as the matrix suction increases; (2) Due to the increase of the pre-consolidation stress, soil compactness increases, and pore size reduces, which makes the water migration more difficult. Therefore, as the sampling depth of soil increases, the air intake increases and the residual water content decreases. (3) Due to the pore size, bottleneck effect and contact angle, the water content of the humidification curve is higher under the same matrix suction, and the soil-water characteristic curve in the humidification test shows obvious hysteresis effect.